A domains‐based approach to meeting social, emotional and mental health needs. Issue 2 (17th June 2019) - O'Brien, Tim; Roberts, Amelia
Abstract: This article focuses on seven interacting research‐informed domains. These domains are grounded in the research literature and have been applied in real world contexts to provide insight into, and an analytical tool for, meeting social, emotional and mental health (SEMH) needs within educational settings. Practitioner researchers applied the domains in a ten‐month knowledge‐exchange programme known as SWERL. Each domain is described in relation to the lived experience of teachers, pupils and schools. The article closes with a case study of how a primary school changed SEMH provision in the areas of 'planning transitions' and 'building relationships' and illuminates the benefits for children, staff and school culture.